Habis Manis Sepah Jadi Uang: Pemanfaatan Ampas Tebu Menjadi Boneka Arang Aktif - Sumiati; Andi Muhammad Irfan Taufan Asfar; Andi Muhamad Iqbal Akbar Asfar; Andi Aswan; Dahniar; Nelly Hasanuddin (Universitas Lancang Kuning, 2021)
In the eyes of the people in Arasoe Village, bagasse does not have a high benefit, it is only used as an embankment in a water channel or allowed to pile up. The bagasse pile is sometimes burned to reduce the quantity in the environment. However, burning bagasse waste is not effective in reducing the accumulation that occurs because the waste of sugarcane is very large and causes air pollution and the result of combustion only produces ash, if it is disposed of into the river it will pollute nature. Community empowerment in utilizing bagasse to become active puppets is a form of counseling by the community service team of STKIP Muhammadiyah Bone which is carried out online. This counseling was attended by 10 people consisting of the PKK group in Arasoe Village, China District, Bone Regency. The activities carried out were in the form of an introduction to the purpose of holding community service activities, presentation of tools and materials and the stages in making activated charcoal dolls. So that the community will be able to implement independently as the final result of this activity.